Factor Risk The incidence of diabetes mellitus in coastal areas Health Center Tondation : Literature Review - Saharudin; Syarifail Palenda; Rasniah Sarumi (Journal of Health Science and Pharmacy, 2025)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels, resulting from the body’s inability to produce sufficient insulin or to utilize insulin effectively. This condition leads to hyperglycemia, which manifests through typical symptoms such as frequent urination in large volumes with a sweet odor, commonly referred to as “sweet urine.” A blood glucose concentration exceeding 200 mg/dL indicates an abnormality in the body’s glucose regulation. Objective: This study aims to identify the risk factors contributing to the incidence of diabetes mellitus in coastal areas. Methods: This research employed a systematic literature review (SLR) design, utilizing a structured library research approach. References were collected from secondary data derived from previous studies. The data sources consisted of scientific articles and journals accessible through the Google Scholar database. Results: The review revealed that factors such as age, sex, occupation, dietary patterns, physical activity, genetic predisposition, and lifestyle were significantly associated with the incidence of DM in coastal areas. In contrast, dietary habits related to specific food consumption and smoking behavior did not show a significant association with DM incidence in these regions. Conclusion: Risk factors contributing to diabetes mellitus in coastal areas include individual characteristics, family history, lifestyle, fruit consumption, and physical activity levels. Conversely, vegetable consumption and general dietary patterns were not identified as primary risk factors. Keywords: diabetes mellitus, characteristics, genetics, physical activity, lifestyle, coastal areas